Trends in Intravenous Magnesium Use and Outcomes for Status Asthmaticus in Children's Hospitals from 2010 to 2017. Issue 7 (17th June 2020) - Mittal, Vineeta; Hall, Matt; Antoon, James; Gold, Jessica; Kenyon, Chen; Parikh, Kavita; Morse, Rustin; Quinonez, Ricardo; II, Ronald J Teufel; Shah, Samir S
Abstract : Intravenous (IV) magnesium is used as an adjunct therapy in management of status asthmaticus with a goal of reducing intubation rate. A recent review suggests that IV magnesium use in status asthmaticus reduces admission rates. This is contrary to the observation of practicing emergency room physicians. The goal of this study was to assess trends in IV magnesium use for status asthmaticus in US children's hospitals over 8 years through a retrospective analysis of children younger than 18 years using the Pediatric Health Information System database. Outcomes were IV magnesium use, inpatient and intensive care unit admission rate, geometric mean length of stay, and 7‐day all‐cause readmission rate. IV magnesium use for asthma hospitalization more than doubled over 8 years (17% vs. 36%; P < .001). Yearly trends were not significantly associated with hospital or intensive care unit admission rate or 7‐day all‐cause readmissions, although length of stay was reduced ( P < .001). Abstract :